1996
DOI: 10.1083/jcb.132.5.945
|View full text |Cite
|
Sign up to set email alerts
|

The neurotrophin receptor, gp75, forms a complex with the receptor tyrosine kinase TrkA.

Abstract: Abstract. The high-affinity NGF receptor is thought to be a complex of two receptors, gp75 and the tyrosine kinase TrkA, but direct biochemical evidence for such an association has been lacking. In this report, we demonstrate the existence of such a gp75-TrkA complex by a copatching technique. Gp75 on the surface of intact cells is patched with an anti-gp75 antibody and fluorescent secondary antibody, the cells are then fixed to prevent further antibody-induced redistributions, and the distribution of TrkA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 52 publications
4
37
2
Order By: Relevance
“…10 recent evidence in TrkB.T1 induces dendritic filopodia via p75 NTR fact indicates a ligand-independent molecular interaction of both TrkB.FL and intracellularly truncated TrkB.FL (resembling TrkB.T1) with the p75 NTR receptor in HEK A293 cells, and also shows a role of these heteromeric receptor complexes in ligand discrimination (Bibel et al, 1999). Similar results have been described with respect to a molecular interaction of TrkA with p75 NTR (Ross et al, 1996;Gargano et al, 1997) and a functional interaction of TrkC receptors with p75 NTR (Hapner et al, 1998) in non-neuronal cells. Our data now provide the first evidence for a possible physiological function of a TrkB-p75 NTR heteromeric receptor in neurons (see above).…”
Section: Trkbt1-induced Morphological Changessupporting
confidence: 73%
“…10 recent evidence in TrkB.T1 induces dendritic filopodia via p75 NTR fact indicates a ligand-independent molecular interaction of both TrkB.FL and intracellularly truncated TrkB.FL (resembling TrkB.T1) with the p75 NTR receptor in HEK A293 cells, and also shows a role of these heteromeric receptor complexes in ligand discrimination (Bibel et al, 1999). Similar results have been described with respect to a molecular interaction of TrkA with p75 NTR (Ross et al, 1996;Gargano et al, 1997) and a functional interaction of TrkC receptors with p75 NTR (Hapner et al, 1998) in non-neuronal cells. Our data now provide the first evidence for a possible physiological function of a TrkB-p75 NTR heteromeric receptor in neurons (see above).…”
Section: Trkbt1-induced Morphological Changessupporting
confidence: 73%
“…Since all the mutant versions of the NGF receptors utilized in this work preserve the transmembrane region, it can be argued that extensive contacts in the intra-or in the extracellular domains are necessary to stabilize the possibly weak interaction of the transmembrane domains. NGF does not modulate the interaction between TrkA and p75 either in the present study or in a previous one (Ross et al, 1996). It is therefore possible that their reciprocal affinity for binding is a property not subjected to regulation; nevertheless, other explanations may hold true.…”
Section: Discussioncontrasting
confidence: 61%
“…It should be noted that recently other authors have demonstrated a direct interaction between p75 and TrkA in the same cell system by using a copatching technique (Wolf et al, 1995;Ross et al, 1996). They have also argued that the ectodomains of p75 and TrkA proteins are responsible for reciprocal interaction, although a small contribution by the intracellular and transmembrane domains was detected (Ross et al, 1996).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations